Estudo clínico e molecular de pacientes com espectro óculo aurículo vertebral - Bragagnolo, Silvia [UNIFESP] (2017)
The Oculoauriculovertebral spectrum (OAVS) comprises a syndromic group, characterized by anomalies involving the first and second pharyngeal arches derivatives. Involvement is usually limited to one side, but bilateral form is known. The phenotype is highly variable, involving ears, eyes, face and neck and other systems and organs too. Objectives: To establish a phenotype-genotype correlation to the OAVS through analysis of molecular and cytogenetic findings from previous selected patients with at least microtia and facial asymmetry. Methods: We performed in each of the selected patients a phenotype, karyotype and CGH-array analysis and correlated to the findings previously reported in the literature. Results: From the 72 patients analyzed, 20 presented with a copy number variation (CNV) region classified as probably pathogenic. Ultimately, we were able to infer 22 different regions of CNV to the OAVS. Conclusions: We could not implicate a single genomic region to this broad phenotype but we were able to observe frequent rearrangements in chromosome 4 and 22. Some of the CNVs regions encompassed genes relevant to this specific phenotype and were also related to other already known diseases. The identification of recurrent rearrangement at 22q11 region in some of our patients reinforces the hypothesis that this would be a candidate region to the OAVS. Furthermore, we characterized in 4 patients another frequent region for rearrangement at the chromosome 4, including it as a possible candidate region as well. Our study suggests that different mechanism of pathogenicity may be involved in the OAVS.